Migration and refugee policies in Germany. New European limits of control? - Ette, Andreas (B. Budrich, 2017)
Internationale Migration ist heute eines der kontroversesten politischen Themen, das innovative Ansätze globaler und regionaler Governance erfordert. Das Buch bietet einen neuen theoretischen Rahmen, um europäische Antworten auf die internationale Migration von Menschen zu verstehen und erklärt die Dynamik der deutschen Migrations- und Flüchtlingspolitik in den letzten zwei Jahrzehnten. Im Gegensatz zu den traditionellen Theorien und ihrer inhärenten Fokussierung auf die nationale politische Sphäre hebt das Buch supranationale und mehrstufige politische Prozesse als zunehmend wichtige Faktoren für die Berücksichtigung nationaler politischer Veränderungen hervor.

International migration is one of the most controversial political topics today which demands innovative approaches of global and regional governance. The book provides a fresh theoretical framework to understand European responses to the international migration of people and explains the dynamics of Germany s migration and refugee policy during the last two decades. Against traditional theories and their inherent focus on the national political sphere, the book highlights supranational and multi-level political processes as increasingly important factors to account for national policy changes. Confronted with the most recent developments of international migration, the study offers students and practitioners the necessary background to participate in today's debates.
Keywords: Bevölkerungsentwicklung; Bevölkerungsstruktur; Einwanderung; Integration; Arbeitsmigration; Ausländischer Arbeitnehmer; Bevölkerungswissenschaft; Zuwanderung; Migration; Europäisierung; Flüchtlingspolitik; Migrationspolitik; Anpassungsprozess; Asylpolitik